Reproducibility Assessment of Zirconia-Based Ceramics Fabricated out of Nanopowders by Electroconsolidation Method - Miroslaw Rucki; Edvin Hevorkian; Jolanta Natalia Latosińska; Vasyl Kolodnitskyi; Leszek Chalko; Dmitrij Morozow; Waldemar Samociuk; Jonas Matijosius; Milan Masař; Tomasz Ryba (Applied Sciences)
The repeatability of the material properties is required to ensure the proper performance of the engineered systems that are constructed using these materials. In this paper, an analysis of the sintered ceria-stabilized zirconia is presented. This material exhibited high mechanical properties, due to the mechanism of strengthening via phase transition. The reproducibility was assessed for the material made out of a starting powder produced by fluoride salt precipitation. To fabricate specimens, a novel electroconsolidation method was used, ensuring a high heating rate, relatively low sintering temperatures, and short holding time. Weibull analysis was performed considering the bending strength of specimens and their microhardness. The obtained values of both shape parameter m and scale parameter σ0 indicated that the ZrO2 stabilized with 5 wt.% CeO2 samples exhibited low variability of strength and hardness. The experimental evidence and statistical analysis reveal an influence of the m-phase, which has lower symmetry and therefore its addition makes ceramic weaker and softer. Furthermore, its progressive replacement by the t-phase, which has higher symmetry, makes ceramic both harder and stronger. Reducing the mol% increases the risk of the appearance of the highest addition of the monoclinic phase; increasing it is unfavorable from the point of view of the sintering process. Statistical and manufacturing evidence suggests that the choice of 5%/mol is optimal.